2015
DOI: 10.4025/cienccuidsaude.v14i1.23259
|View full text |Cite
|
Sign up to set email alerts
|

<b> Educação em saúde: uma estratégia de intervenção frente ao câncer de mama / Health education: a strategy for action against breast cancer

Abstract: RESUMO O objetivo foi avaliar a efetividade da intervenção educativa sobre câncer de mama com usuárias da Estratégia de Saúde da Família (ESF), mediante comparações do pré e pós-teste. Estudo quase-experimental, desenvolvido com 84 mulheres a partir dos 18 anos. A coleta ocorreu em Unidades de Saúde da Família do município de Sirinhaém-Pernambuco, no período de maio a setembro de 2013, através de três etapas: aplicação do pré-teste, realização da atividade de educação em saúde acerca da temática e aplicação do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
1
0
3
Order By: Relevance
“…The findings found in this study are supported by other studies that have also shown promising results in increasing women's knowledge about breast cancer, risk factors and diagnostic methods for early detection from the use of educational strategies (13)(14)(15) . It should be noted that different educational strategies were proposed in these studies, such as the development of focus groups, the application of an educational manual, a community intervention program, and others.…”
Section: Discussionsupporting
confidence: 88%
“…The findings found in this study are supported by other studies that have also shown promising results in increasing women's knowledge about breast cancer, risk factors and diagnostic methods for early detection from the use of educational strategies (13)(14)(15) . It should be noted that different educational strategies were proposed in these studies, such as the development of focus groups, the application of an educational manual, a community intervention program, and others.…”
Section: Discussionsupporting
confidence: 88%
“…Such measures should strengthen the search for health services, motivating access, reducing the questions related to their efficiency and strengthening the strategies and programs for guidance and stimulation. 10 Women's broad access to clear, consistent, and culturally appropriate information should be an initiative of health services at all levels, especially in Primary Health Care (PHC). It is known that prevention for breast cancer can be primary (linked to lifestyle changes) and secondary (based on Clinical Breast Examination (CBE) measures and screening through biannual mammography).…”
Section: Discussionmentioning
confidence: 99%
“…Quando o diagnóstico não é feito precocemente, a doença pode cursar gravemente ao ponto de a mulher precisar passar por uma mastectomia, que visa a retirada total ou parcial da glândula mamária com intuito de aumentar a expectativa de vida de mulheres consideradas de alto risco (14) . Todavia esse procedimento cirúrgico representa uma experiência traumática para mulher afetando suas interrelações e acarretando grandes impactos em sua saúde psicológica (15) , podendo afetar na adesão à terapia com antineoplásico oral.…”
Section: Discussionunclassified